2020
DOI: 10.26508/lsa.202000847
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-based quorum sensing systems in Paenibacillus polymyxa

Abstract: Paenibacillus polymyxa is an agriculturally important plant growth–promoting rhizobacterium. Many Paenibacillus species are known to be engaged in complex bacteria–bacteria and bacteria–host interactions, which in other species were shown to necessitate quorum sensing communication. However, to date, no quorum sensing systems have been described in Paenibacillus. Here, we show that the type strain P. polymyxa ATCC 842 encodes at least 16 peptide-based communication systems. Each of these systems is comprised o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Of the 3529 conservative candidate RRNPP QSSs, we found that 2793 are chromosomal (on 941 different chromosomes), 222 are plasmidic (on 172 different plasmids), 505 are predicted to be prophage-encoded (on 219 predicted intact prophages, 102 questionable prophages and 176 incomplete prophages) and 9 are encoded by genomes isolated from free temperate bacteriophages (on 8 distinct bacteriophages) ( Table S2 ). Although the presence of multiple QSSs on single chromosomes is not rare (8,21) due to the selective pressure that may exist for the acquisition of additional subpopulation-specific QSSs (41,42), only 1 MGE (Bacillus phage phi3T) has been previously reported to encode two RRNPP QSSs (43). Here, we report the identification of 30 plasmids and 8 (pro)phages encoding multiple candidate RRNPP QSSs (up to 5 in the pBMB400 plasmid of Bacillus thuringiensis serovar kurstaki str.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 3529 conservative candidate RRNPP QSSs, we found that 2793 are chromosomal (on 941 different chromosomes), 222 are plasmidic (on 172 different plasmids), 505 are predicted to be prophage-encoded (on 219 predicted intact prophages, 102 questionable prophages and 176 incomplete prophages) and 9 are encoded by genomes isolated from free temperate bacteriophages (on 8 distinct bacteriophages) ( Table S2 ). Although the presence of multiple QSSs on single chromosomes is not rare (8,21) due to the selective pressure that may exist for the acquisition of additional subpopulation-specific QSSs (41,42), only 1 MGE (Bacillus phage phi3T) has been previously reported to encode two RRNPP QSSs (43). Here, we report the identification of 30 plasmids and 8 (pro)phages encoding multiple candidate RRNPP QSSs (up to 5 in the pBMB400 plasmid of Bacillus thuringiensis serovar kurstaki str.…”
Section: Resultsmentioning
confidence: 99%
“…even discovered that some temperate bacteriophages encode RRNPP QSSs, namely the “arbitrium” systems that guide the lysis-lyogeny decision upon Bacillus infection (18,19). Recently, two other chromosomal RRNPP QSSs have been experimentally validated: the QsrB-QspB system that delays sporulation and solvent formation in Clostridium acetobutylicum (20) and the AloR13-AloP13 sporulation-regulator in Paenibacillus polymyxa (21). As important the experimentally-validated RRNPP QSSs are in the regulation of the biology of their encoding microbial entity, they represent only the tip of the iceberg.…”
Section: Introductionmentioning
confidence: 99%
“…3A). These results especially make sense in light of a recently identified chromosomal RRNPPtype QSS, shown to regulate the expression of its adjacent spo0E gene in a density dependent manner (31). The functions of the other (pro)phage-encoded candidate QSSs were difficult to predict from their genomic contexts and would require further exciting functional studies to characterize which biological processes they might regulate in a (pro)phage-density dependent manner.…”
Section: Bacteriophages Have Evolved Many Different Genetic Systems Predicted To Dynamically Modulate the Bacterial Sporulation Initiatiomentioning
confidence: 90%
“…Second, it consists in retaining only the coding sequences of those putative receptors that are located directly adjacent to the coding sequence of a candidate communication pro-peptide, defined as a small protein of 15-65 aa predicted to be secreted via the SEC-translocon by the stringent SignalP software (Fig. 1 (31).…”
Section: Large-scale Query Of the Rrnpp-type Signature Reveals Hundreds Of Candidate Qsss Encoded By Free Bacteriophages Or Prophagesmentioning
confidence: 99%
See 1 more Smart Citation